Exploring the impact of social media humor related to the COVID-19 pandemic: a systematic literature review on themes, coping mechanisms, critiques and linguistic devices - Sulaiman Mohammad Shlash Alkaraki; Norhayati Binti Alias; Marlyna Maros (Cogent Arts & Humanities)
Amid the global COVID-19 pandemic, the use of humor on social media has emerged as a significant area of study. Nevertheless, a thorough analysis that brings together the most recent research on humor related to the pandemic is required. This systematic literature review is designed to conduct a thorough analysis of existing research on COVID-19 humor on social media, specifically its themes and categories, coping mechanisms, effects on confidence in government institutions, and the use of specific linguistic devices. It examines the role of humor in the COVID-19 pandemic, providing a detailed descriptive qualitative analysis of 49 worldwide studies between 2019 and 2022. The findings reveal that humor serves as a coping mechanism, assisting individuals in navigating the challenges and uncertainties of the pandemic, thereby promoting mental well-being. Humor emerged as a powerful tool to critique government actions, uncover inefficiencies, and shape public discourse. Linguistic devices, including wordplay, irony, satire, and parody, play a crucial role in conveying messages and emotions related to the pandemic. However, the review highlights the potential for humor to propagate harmful stereotypes and contribute to discrimination. Future research should explore the cultural and social variations in humor styles, coping mechanisms, and the effectiveness of humor globally.